Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1140/epjc/s10052-018-5653-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of MeV-scale dark matter utilizing germanium internal amplification for the charge created by the ionization of impurities

Abstract: Light, MeV-scale dark matter (DM) is an exciting DM candidate that is undetectable by current experiments. A germanium (Ge) detector utilizing internal charge amplification for the charge carriers created by the ionization of impurities is a promising new technology with experimental sensitivity for detecting MeV-scale DM. We analyze the physics mechanisms of the signal formation, charge creation, charge internal amplification, and the projected sensitivity for directly detecting MeV-scale DM particles. We pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 100 publications
2
65
0
Order By: Relevance
“…This enables Ge detectors to be used for detecting low mass WIMPs of a few GeV/c 2 . More recently, a Ge detector utilizing internal charge amplification for the charge carriers created by the ionization of impurities has been demonstrated theoretically to be a promising new technology for detecting MeV-scale dark matter [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enables Ge detectors to be used for detecting low mass WIMPs of a few GeV/c 2 . More recently, a Ge detector utilizing internal charge amplification for the charge carriers created by the ionization of impurities has been demonstrated theoretically to be a promising new technology for detecting MeV-scale dark matter [31].…”
Section: Introductionmentioning
confidence: 99%
“…In order to directly detect MeV-scale dark matter, a detector with the ability to measure a single electron-hole (e-h) pair is required, since both electronic recoils and nuclear recoils induced by MeV-scale dark matter are in the range of sub-eV to 100 eV [1]. Mei et al has suggested direct detection of MeV-scale DM utilizing germanium internal charge amplification (GeICA) for the charge created by the ionization of impurities [31]. GeICA can reach a detection energy threshold as low as 0.1 eV, allowing a large portion of both electronic recoils and nuclear recoils in the range of sub-eV to 100 eV [1,31] induced by DM to be accessible.…”
Section: Introductionmentioning
confidence: 99%
“…Dark matter at the MeV scale is an interesting possibility, offering a rich phenomenology [4]. The topic has witnessed increasing interest in light of null results in the search for WIMPs [17] and of the many upcoming experimental probes for MeV-scale dark matter [18][19][20][21][22][23]. Several MeV dark matter studies have been conducted in the literature, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in Sec. III C, adding dopants to the Germanium crystal can lower the ionization energy and probe lower values of M χ [43]. The impact of the discovery limit for several doping techniques could be calculated in order to probe lower DM masses.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to lower the band-gap energy by adding dopants to the Germanium crystal as discussed in [43]. Phonons with ionization energies as low as ∼0.01 eV can ionize or excite impurities and create charge carriers, though the sub-eV recoil energies are small enough that they can be obscured by electronic noise of signal digitization.…”
Section: Minimum Recoil Energy Thresholdmentioning
confidence: 99%